Characterization of novel biodegradable elastomers - Chan, Paul Ng Poh Huat. (2009)
Polymers have been rapidly replacing other materials in many applications, even in the biomedical aspect, e.g. replacing a stainless steel heart stent with a biodegradable polymeric one, hence there is a need to find polymers with better properties.